Hubungan Konsumsi Minuman Ringan dan Kopi dengan Kejadian Hipertensi Remaja - Romadhiyana Kisno Saputri; Hadiyatul Lilfitriyani (STIKes Karsa Husada Garut, 2021)
Adolescents eating habbit can be affected by life style, including excessive consumption of soft drinks and coffee. Soft drinks and coffee contains some potentially harmful substances which can cause hypertension, such as simple sugar, synthetic sweeteners, acids and caffeine. Hypertension on adolescent can continously brougt it until their adulthood and will have a higher risk of morbidity and mortality. This study aimed to determine the relationship between soft drinks consumption and coffe consumption to hypertension rate in adolescents. It is a descriptive analytic method study using cross sectional design. The sample in this study is 72 respondents of UNUGIRI students that collected by total sampling methods. Data collected including soft drinks consumption, coffee consumption and blood pressure. Fisher Exact test was used in data analysis. Result showed 61,6% respondents consume soft drinks oftenly, and 79,2% respondents consume coffee rarely. About 16.7% of respondents are classified as hypertension. The result indicated that there is no relationship between soft drinks consumptions and hypertension and no relationship between coffee consumptions and hypertension. Perhaps, the content of sodium and sugar in soft drinks which consumed by respondents are still within safe limits. Key words: Soft Drinks, Coffee, Hypertension, Adolescent